Vertex Szeged index of crystal cubic carbon structure. (3rd October 2019) - Yang, Hong; Naeem, Muhammad; Baig, Abdul Qudair; Shaker, Hani; Siddiqui, Muhammad Kamran
Abstract: Graph theory plays an important role in modeling and designing any chemical structure or network. The molecular topological indices are the numerical invariants of a molecular graph and are very useful for predicting their bioactivity. In this paper we have computed vertex-Szeged index, vertex PI index, the vertex Szeged geometricarithmetic index and the weighted vertex Szeged indexfor the crystal cubic structure CCC ( n ) of carbon.